Path-Computation-Element-Based Architecture for Interdomain MPLS Overview and Performance. - Dasgupta, S.
The Path Computation Element Working Group at the Internet Engineering Task Force is chartered to specify a PCE-based architecture for the path computation of interdomain MPLS- and GMPLS-based traffic engineered label switched paths. In this architecture, path computation does not occur at the head-end LSR, but on another path computation entity that may not be physically located on the head-end LSR. This method is greatly different from the traditional "per-domain" approach to path computation. This article presents analysis and results that compare performance of the PCE architecture with the current state-of-the-art approach. Detailed simulations are undertaken on varied and realistic scenarios where preliminary results show several performance benefits from the deployment of PCE. To provide a complete overview of significant development taking place in this area, milestones and progress at the IETF PCE WG are also discussed.
Keywords: Internet Engineering Task Force; Path Computation Element Working Group; Generalized multiprotocol label switching; Head-end LSR; Interdomain MPLS-GMPLS traffic engineering; Label switched paths; Path-computation-element-based architecture